(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Businesses and other organisations have recommended their staff to work from home as aprecaution in view of the recent outbreak of the new coronavirus COVID-19. However, due of remotework, employees have been exposed to new security vulnerabilities. Additionally, the number of datagathered from numerous sources has expanded due to the fast worldwide adoption of COVID-19. Inorder for workers to effectively complete their jobs when working from home, Cloud computing servicesare the primary method of computing for them. The cloud computing environment (CCE) is an unsunghero in the COVID-19 pandemic tragedy. It comprises of the quick service delivery methods that followthe development of quickly deployable data maintenance apps. Researchers continue to face challengesrelated to CCE research, including data security, making CCE apps accessible and making it easier forpeople to utilise CCE apps in their daily lives. It seems to be the first research to evaluate the effects ofthe COVID-19 pandemic on CCE in more detail. The risks of working from home while the COVID-19epidemic is underway are also addressed in this article.